UPAYA KEPALA SEKOLAH DALAM MENYUKSESKAN PENERAPAN KURIKULUM MERDEKA - Mohamad Muspawi; Salsabila Janati; Dwi Aryati; Mika; Carmelira Angel Gulo (LPPM Universitas Cipta Mandiri, 2024)
This research discusses the efforts of sokalah leaders in implementing the curriculum at the Nurul Ilmi Jambi Integrated Islamic High School (SMAIT). The research method used is a quantitative research method. Implementation of the Independent Curriculum is the main focus of school principals. The initial steps taken involved teacher training, creating a common perception regarding the importance of the Independent Curriculum, and building cooperation both internally and externally. Even though it has only been implemented in class 10 for the 2023 academic year, SMAIT Nurul Ilmi Jambi has tried to be an example for other schools in adopting the Independent Curriculum with the support of supervisors and regular consultations. However, in the process of implementing the Independent Curriculum, SMAIT Nurul Ilmi Jambi faced several obstacles. This includes changes in learning design, creating teaching modules, as well as determining students' areas of expertise in phase F (grades 11-12). However, schools are trying to overcome this obstacle by involving teachers in independent learning platforms, sharing experiences through Subject Teacher Conferences (MGMP), and planning to improve facilities and infrastructure. Apart from that, they also encourage the development of students' interests and talents through extracurricular activities and collaborate with psychology institutions to identify student potential since grade 10